Nurturing Indonesian Indetity Througt Intercultural Communication In Migrant Children - Aminatuz Zuhriyah; Zamawi Chaniago; Eli Purwati; Krisna Megantari (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Intercultural communication is key in shaping national identity, especially for migrant children growing up in multicultural environments. This study aims to uncover the effectiveness of intercultural communication strategies in shaping the national identity of Indonesian migrant children in Malaysia. Through a qualitative approach, this study found that the Hulu Kelang Guidance Center (SBHK) has successfully implemented various innovative strategies. Active participation in activities related to the Indonesian language and culture significantly enhances the sense of pride in the national identity of migrant children. This study provides a new contribution by identifying the key factors that influence the success of intercultural communication strategies in the context of non-formal education for migrant children. This finding could serve as a foundation for the development of more effective non-formal education programs that facilitate the social and cultural integration of migrant children.